The Effectiveness of Extensive Reading with Different Modes of Journal Writing on EFL University Students' Writing Fluency and Accuracy - Shu-Chu Chen (National Taipei University of Education, 2023)
This study, adopting a quasi-experimental research design, investigated the relative effectiveness of a 15-week extensive reading plus different modes of journal writing on EFL university students' writing fluency and accuracy. One hundred and eleven participants, with similar initial TOEIC English proficiency levels, were assigned to three experimental groups and one control group. One experimental group participated in an extensive reading plus Chinese journal writing program. The second group was involved in an extensive reading plus English journal writing program. The third group did extensive reading plus English journal writing and teacher corrective feedback while the control group received regular English class instruction. The instruments included a TOEIC English proficiency test, a writing pretest, and a posttest. Students' writing fluency and accuracy were evaluated by two native speakers of English. Data were analyzed by ANOVA with repeated measures to assess the participants' writing fluency and accuracy before and after the intervention. Results showed that extensive reading plus English journal writing with or without corrective feedback significantly enhanced posttest writing fluency from the pretest. Both programs yielded a significantly better effect on posttest writing fluency than the regular class and extensive reading plus Chinese journal writing. For writing accuracy, while all three interventional programs significantly improved posttest writing accuracy from the pretest, extensive reading plus English journal writing with corrective feedback was more effective than the regular class and extensive reading plus English or Chinese journal writing. The results offered empirical support for the application of relevant theoretical frameworks, including input, output, and skill acquisition theories. The research held valuable implications for future extensive reading curriculum design incorporating diverse journal writing modes and teacher feedback to enhance students' writing performance.